Gestão da micro propriedade rural sob a ótica do Diagrama Causa-Efeito de Ishikawa - Pompermaier, Ana Paula (2017)
Micro-rural property must be treated as a company, which needs to deal with the various problems, related to failures in the definition of productive processes, defects in products or services and other actions that interfere. In this sense, the present work had as its objective to propose a plan of action, based on the methodology proposed by Ishikawa, that allows the coordination of productive processes in a micro rural property. For the emphasis of this case study, a research was developed on a Micro Rural Property located in the municipality of Capanema/ PR. During the development of this study the methods of bibliographic research on Rural Enterprises, Milk Sector, Ishikawa Matrix, Action Plans and Organizational Routines were used as stated in the theoretical framework. The information was collected in the form of a semi-structured interview and the collection of documentary data. Regarding the analysis of the data, it was done in a qualitative way, and all the information obtained was evaluated and transcribed for a better understanding and verification of the information, pointing out that the methodology proposed by Ishikawa identified the main effects and causes pointed out by rural micro entrepreneurs. Action plans have been developed to coordinate, which should be taken to reduce the causes that affect the productive process of micro-rural property with the description of the person responsible for its compliance and the stipulated date for its implementation. The methodology was effective and determinant in the identification of the lack of a formal planning culture in small rural enterprises, the matrices proposed by each of the involved in the rural property, was fundamental to visualize how each one sees certain problems that interfere in the productive process. And encourage that the producer needs to know tools and the importance of this exercise in his property. As a suggestion for future work the application of the six basic quality tools together with Ishikawa Diagram.